1981
DOI: 10.1111/j.1525-1594.1981.tb03996.x
|View full text |Cite
|
Sign up to set email alerts
|

Axial Changes of Blood and Plasma Flow, Pressure, and Cellular Deposition in Capillary Plasma Filters

Abstract: The ability to separate plasma on-line from whole blood by membranes has generated interest in applying this process to source plasma collection and to the therapeutic treatment of various disease states. The availability of capillary membrane devices in particular has prompted investigations in these areas. The deposition of blood cellular elements has required the investigation of those parameters related to fluid and mass flux. Analytical solutions relating blood flow rate, filtration rate, and pressure and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The inverse relationship of cell radius has been noted to correlate in comparing bovine and dog blood; however, the correlation is not necessarily to the second power. The deposition parameter theory has been a useful guide to assess the axial changes in blood cell deposition (11) although the exact value of the parameter is variable and not reliable in design optimization.…”
Section: Membrane Plasma Separator Considerationsmentioning
confidence: 99%
“…The inverse relationship of cell radius has been noted to correlate in comparing bovine and dog blood; however, the correlation is not necessarily to the second power. The deposition parameter theory has been a useful guide to assess the axial changes in blood cell deposition (11) although the exact value of the parameter is variable and not reliable in design optimization.…”
Section: Membrane Plasma Separator Considerationsmentioning
confidence: 99%
“…Considering the interaction forces between particles, Zydney [16] applied shear-induced diffusion in place of Brownian diffusion in concentration polarization theory to predict the filtration process of red blood cells and found that the prediction results were in good agreement with the experimental values. In addition, assuming a balance between inertial lift and hydrodynamic force in equilibrium, some researchers [17][18][19] proposed models that apply inertial lift instead of particle diffusion. According to experimental verification, the inertial lift theory is generally applied to solid particles larger than 30 µm [20].…”
Section: Introductionmentioning
confidence: 99%